Recombinant extracellular domain of the three major subunits of GABA(A) receptor show comparable secondary structure and benzodiazepine binding properties - Shi, Haifeng (Cold Spring Harbor Laboratory Press, 2003)
The three most widely expressed subunits of the GABA(A) receptor are α(1), β(2), and γ(2) subunits, and the major isoform in the human brain is a pentameric receptor composed of 2α(1)2β(2)1γ(2). Previously, we overexpressed the extracellular domain Q28-R248 of GABA(A) receptor α(1) subunit. In the present study, the homologous extracellular domains Q25-G243 of GABA(A) receptor β(2) subunit and Q40-G273 of γ(2) subunit were also obtained through overexpression in Escherichia coli. Successful production of recombinant β(2) and γ(2) subunit receptor protein domains facilitates the comparison of structural and functional properties of the three subunits. To this end, the secondary structures of the three fragments were measured using CD spectroscopy and the β-strand contents calculated to be >30%, indicating a β-rich structure for all three fragments. In addition, the benzodiazepine (BZ)-binding affinity of the recombinant fragments were measured using fluorescence polarization to be 2.16 μM, 3.63 μM, and 1.34 μM for the α(1), β(2), and γ(2) subunit fragments, respectively, indicating that all three homomeric assemblies, including that of the β(2) subunit, generally not associated with BZ binding, can bind BZ in the micromolar range. The finding that the BZ binding affinity of these recombinant domains was highest for the γ(2) subunit and lowest for the β(2) subunit is consistent with results from previous binding studies using hetero-oligomeric receptors. The present results exemplify the effective approach to characterize and compare the three major subunits of the GABA(A) receptor, for two of which the overexpression in E. coli is reported for the first time.